High Temperature SELMA: Evolution of DNA-Supported Oligomannose Clusters Which Are Tightly Recognized by HIV bnAb 2G12 - Temme, J. Sebastian (American Chemical Society, 2014)
[Image: see text] SELMA (SELection with Modified Aptamers) is a directed evolution method which can be used to develop DNA-supported clusters of carbohydrates in which the geometry of clustering is optimized for strong recognition by a lectin of interest. Herein, we report a modification of SELMA which results in glycoclusters which achieve dramatically stronger target recognition (100-fold) with dramatically fewer glycans (2–3-fold). Our first applications of SELMA yielded clusters of 5–10 oligomannose glycans which were recognized by broadly neutralizing HIV antibody 2G12 with moderate affinities (150–500 nM K(d)’s). In the present manuscript, we report glycoclusters containing just 3–4 glycans, which are recognized by 2G12 with K(d)’s as low as 1.7 nM. These glycoclusters are recognized by 2G12 as tightly as is the HIV envelope protein gp120, and they are the first constructs to achieve this tight recognition with the minimal number of Man(9)units (3–4) necessary to occupy the binding sites on 2G12. They are thus of great interest as immunogens which might elicit broadly neutralizing antibodies against HIV.